1999
DOI: 10.2337/diabetes.48.5.1088
|View full text |Cite
|
Sign up to set email alerts
|

Isolated low HDL cholesterol: an insulin-resistant state only in the presence of fasting hypertriglyceridemia.

Abstract: Individuals with isolated low HDL cholesterol are at increased risk of coronary artery disease. It has been reported previously that this is an insulin-resistant state. We analyzed data from the 1992 Singapore National Health Survey with the objective of defining the clinical and metabolic parameters associated with isolated low HDL cholesterol. A total of 3,568 individuals were selected by stratified random sampling. Subjects with low HDL cholesterol (<0.9 mmol/l) and "ideal" total cholesterol (<5.2 mmol/l) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 0 publications
7
20
0
1
Order By: Relevance
“…Thus, insulin resistance was found in both isolated hypertriglyceridemia and hypertriglyceridemia with low HDL cholesterol. This finding fits some previous studies such as Tai et al (1999) who found that isolated low HDL cholesterol was an insulin-resistant state only in the presence of fasting hypertriglyceridemia 23) . Schmidt et al (1999) commented that the lipid pattern of high triglyceride and low HDL cholesterol was a feature of inflammation and they argued that insulin resistance was due to related inflammatory cytokines 24) .…”
Section: Discussionsupporting
confidence: 80%
“…Thus, insulin resistance was found in both isolated hypertriglyceridemia and hypertriglyceridemia with low HDL cholesterol. This finding fits some previous studies such as Tai et al (1999) who found that isolated low HDL cholesterol was an insulin-resistant state only in the presence of fasting hypertriglyceridemia 23) . Schmidt et al (1999) commented that the lipid pattern of high triglyceride and low HDL cholesterol was a feature of inflammation and they argued that insulin resistance was due to related inflammatory cytokines 24) .…”
Section: Discussionsupporting
confidence: 80%
“…After adjustment for the differences in height and weight between LBW and NBW subjects, the diastolic blood pressure (DBP) was significantly higher in the LBW subjects (PZ0.01). There was no difference in the BMI or skinfold thickness between the two groups, and in general, all participants were healthy with total cholesterol, LDL-cholesterol and blood pressure measurements within the normal range, except for a mean low HDL-cholesterol level, which was present in both groups and is a common phenomenon in the Indian population (19). In our study, the subjects were not recruited according to gestational age, a factor that has previously been demonstrated to represent a reason for risk (i.e.…”
Section: Resultsmentioning
confidence: 98%
“…17,18 Hyperuricemia and hypertriglyceridemia are suggested to be associated with insulin resistance syndrome. [22][23][24] The association between insulin resistance, hyperuricemia, and hypertriglyceridemia are complicated. This might be expected from the fact that uric acid production is linked to glycolysis and that glycolysis is controlled by insulin.…”
Section: Discussionmentioning
confidence: 99%